Optimal inflation with corporate taxation and financial constraints - Daria Finocchiaro; Giovanni Lombardo; Caterina Mendicino; Philippe Weil (Sveriges Riksbank, 2017)
How does inflation affect the investment decisions of financially constrained firms in the presence of corporate taxation? Inflation interacts with corporate taxation via the deductibility of i) capital expenditures and ii) interest payments on debt. Through the first channel, inflation increases firms' taxable profits and further distorts their investment decisions. Through the second, expected inflation affects the effective real interest rate and stimulates investment. When debt is collateralized, the second effect dominates. Therefore, present a tax-advantage to debt financing, positive long-run inflation enhances welfare by mitigating or even eliminating the investment distortion.
Keywords: E31; E43; E44; E52; G32; 330; optimal monetary policy; Friedman rule; credit frictions; tax benefits of debt